2008
DOI: 10.1007/s15010-008-7223-z
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Serious Infection Caused by Aerococcus urinae: A Patient with Spontaneous Bacterial Peritonitis and Two Patients with Bacteremia

Abstract: Aerococcus urinae (A. urinae) is an unusual urinary tract pathogen [1][2][3], which is also reported in case of endocarditis [1,[3][4][5], septicemia [6][7][8][9], balanitis and phlegmon [1], lymphadenitis [10], and spondylodiscitis [11] in elderly patients with local or systemic predisposing conditions such as neutropenia and prostatic diseases. A. urinae is a grampositive, catalase-negative, microaerophilic, alpha-hemolytic coccus, growing predominately in tetrads and clusters. A. urinae is usually susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Other, less common, presentations of invasive infection are peritonitis in patients receiving peritoneal dialysis [45,46], vertebral osteomyelitis [2,47], soft-tissue infections in the genital area [2,48,49], postpartum infection [50], odontogenic infection [51], joint infections [17,52] and postoperative infection [53].…”
Section: Other Invasive Aerococcal Infectionsmentioning
confidence: 99%
“…Other, less common, presentations of invasive infection are peritonitis in patients receiving peritoneal dialysis [45,46], vertebral osteomyelitis [2,47], soft-tissue infections in the genital area [2,48,49], postpartum infection [50], odontogenic infection [51], joint infections [17,52] and postoperative infection [53].…”
Section: Other Invasive Aerococcal Infectionsmentioning
confidence: 99%
“…Aerococcus urinae is known to colonize the human urinary tract and may cause symptomatic UTI [ 3 ], infective endocarditis [ 4 ] and bacteremia [ 5 ]. However, sepsis due to UTI by A. urinae is not commonly recognized in clinical settings and inadequate treatment of this infection has been linked to fatal outcomes and severe complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although infections are mainly described in men, some cases of cystitis or invasive disease were reported in women. USA and French studies reported respectively 26 and 22 women over 65 years of age with predisposing factor affected by mild UTI [5, 6] , whereas only four cases of bacteraemia were described in women aged between 55 to 89 year-old with predisposing factor (myeloma, diabetes, disseminated sclerosis) [2, 3, 6, 11] . Our patient had no known risk factor for UTI, except pregnancy.…”
mentioning
confidence: 99%